2015
DOI: 10.1371/journal.pntd.0004033
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatic Heart Disease-Attributable Mortality at Ages 5–69 Years in Fiji: A Five-Year, National, Population-Based Record-Linkage Cohort Study

Abstract: BackgroundRheumatic heart disease (RHD) is considered a major public health problem in developing countries, although scarce data are available to substantiate this. Here we quantify mortality from RHD in Fiji during 2008–2012 in people aged 5–69 years.Methods and FindingsUsing 1,773,999 records derived from multiple sources of routine clinical and administrative data, we used probabilistic record-linkage to define a cohort of 2,619 persons diagnosed with RHD, observed for all-cause mortality over 11,538 perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 30 publications
1
41
0
Order By: Relevance
“…In a study from Fiji of 2619 people followed up during 2008 to 2012, the age-standardized death rate was 9.9 (95% CI, 9.8–10.0) per 100 000, or over twice the GBD 2013 estimate. 8a …”
Section: Valvular Diseasesmentioning
confidence: 99%
“…In a study from Fiji of 2619 people followed up during 2008 to 2012, the age-standardized death rate was 9.9 (95% CI, 9.8–10.0) per 100 000, or over twice the GBD 2013 estimate. 8a …”
Section: Valvular Diseasesmentioning
confidence: 99%
“…Fiji has a very high burden of RHD, with a prevalence of definite RHD of 7–8 per 1000 on echocardiographic screening of school-aged children 14 15. RHD is one of the leading causes of mortality in children and young adults 16. The Fiji Ministry of Health and Medical Services operates a register-based RHD control programme.…”
Section: Methodsmentioning
confidence: 99%
“…Another country in Oceania with a high RHD prevalence is Fiji; a recent study of RHD-associated deaths there found that RHD is responsible for a significant premature loss of human life 10. The 50% RHD mortality under 40 years in Fiji directly affects economic productivity in young adulthood,10 the age group on which economies thrive.…”
Section: Global Health Problem Analysismentioning
confidence: 99%
“…The 50% RHD mortality under 40 years in Fiji directly affects economic productivity in young adulthood,10 the age group on which economies thrive. A particularly poignant case by Steer et al 11 indicates the importance of healthcare professional training to recognise RHD in Fiji.…”
Section: Global Health Problem Analysismentioning
confidence: 99%